2022
DOI: 10.1002/ctm2.986
|View full text |Cite
|
Sign up to set email alerts
|

S100A14: A novel negative regulator of cancer stemness and immune evasion by inhibiting STAT3‐mediated programmed death‐ligand 1 expression in colorectal cancer

Abstract: S100A14 expression is downregulated in PD-L1 high colorectal cancer cells, enabling them to have CSC-like phenotypes and immune-suppressive capacities.• S100A14 inhibits PD-L1 expression by directly interacting with STAT3 and inducing its proteasomal degradation.• S100A14 is a potential marker for predicting prognosis and the antitumor response to PD-L1 blockade and chemotherapy in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Several studies have declared that other potential biomarkers are related to the immunoevasive microenvironment of CRC. Lee et al [ 60 ] identified that S100A14 inhibits STAT3-mediated PD-1 expression and the phenotype of tumor stem cells, promotes CD8 + T-cell-mediated cytotoxicity, inhibits immune evasion, and restores chemosensitivity. Thus, targeting S100A14 is likely an effective strategy for preventing CRC progression, and S100A14 could be regarded as a promising indicator for anti-PD-L1 immunotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have declared that other potential biomarkers are related to the immunoevasive microenvironment of CRC. Lee et al [ 60 ] identified that S100A14 inhibits STAT3-mediated PD-1 expression and the phenotype of tumor stem cells, promotes CD8 + T-cell-mediated cytotoxicity, inhibits immune evasion, and restores chemosensitivity. Thus, targeting S100A14 is likely an effective strategy for preventing CRC progression, and S100A14 could be regarded as a promising indicator for anti-PD-L1 immunotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is noteworthy that some of these 29 specific single-cell marker genes have been studied in tumor immunotherapy( Macor et al, 2015 ; Strati et al, 2017 ; Shen et al, 2021 ; Ahmed et al, 2022 ; Min et al, 2022 ), but their role in the response of CRC to immunotherapy is still unclear. Combined with the results of CellMiner, it is suggested that these genes may be potential synergistic targets for enhancing the sensitivity of immunotherapy in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…EMT induced PD-L1 expressed on CSCs via EMT/b-catenin/STT3/PD-L1 signaling axis, and targeting EMT/b-catenin/STT3/PD-L1 axis may downregulate PD-L1 (40). In colorectal cancer, PD-L1 can trigger CSC-like characteristics and chemoresistance in CRC cells (41). PD-L1 overexpressed on CD133 + colorectal CSCs and EMT enable CSCs to invade and metastasize (37).…”
Section: Elevated Expression Of Immune Checkpoint Moleculesmentioning
confidence: 99%